2012
DOI: 10.1371/journal.ppat.1002649
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Suppression of HIV by Antigen Specific T Cells Derived from Engineered Hematopoietic Stem Cells

Abstract: The HIV-specific cytotoxic T lymphocyte (CTL) response is a critical component in controlling viral replication in vivo , but ultimately fails in its ability to eradicate the virus. Our intent in these studies is to develop ways to enhance and restore the HIV-specific CTL response to allow long-term viral suppression or viral clearance. In our approach, we sought to genetically manipulate human hematopoietic stem cells (HSCs) such that they differentiate into mature CTL that will kill HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 55 publications
2
88
0
Order By: Relevance
“…28 We further demonstrated that these HIV-specific CTLs could effectively lower viral loads following HIV infection. These cells underwent normal developmental processes, including their maturation into T cells in the human thymus, and responded to HIV infection in vivo in a highly active and normal manner.…”
Section: Fig 1 Hiv-specific Chimeric Antigen Receptors (Cars)mentioning
confidence: 76%
See 3 more Smart Citations
“…28 We further demonstrated that these HIV-specific CTLs could effectively lower viral loads following HIV infection. These cells underwent normal developmental processes, including their maturation into T cells in the human thymus, and responded to HIV infection in vivo in a highly active and normal manner.…”
Section: Fig 1 Hiv-specific Chimeric Antigen Receptors (Cars)mentioning
confidence: 76%
“…[27][28][29] We determined that the modification of a human HSC with a lentiviral vector containing an anti-HIV TCR can direct the differentiation of mature, polyfunctional HIV-specific T cells in human thymic tissue in vivo in the SCID-hu mouse, a humanized mouse model that recapitulates human T cell development and thymic selection. 27 These cells, carrying the transgenic anti-HIV TCR, survived hematopoietic differentiation and thymopoiesis and developed into cells capable of killing HIV-infected cells ex vivo.…”
Section: Fig 1 Hiv-specific Chimeric Antigen Receptors (Cars)mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, few of these techniques have entered into clinical trials and give hope for a promising future [152]. Apart from their use in therapeutic strategies, techniques of gene therapy are being evaluated in DNA vaccines for prophylactic use and also in some of the strategies of 'immune therapy' [156].…”
Section: Dna Manipulationmentioning
confidence: 99%